Explorative Study on The Impact of Work From Home (WFH) on the Performance of GPAI Semarang District in Covid-19 Pandemic Situation - Abdul Khamid; Aida Dwi Rahmawati (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2020)
The purpose of this research was to find information related to the implementation of Work From Home (WFH) on GPAI’s performance in the Covid-19 pandemic situation. This research was conducted by applying qualitative methods. Respondents were randomly selected, namely 10 GPAI from 10 sub-districts in Semarang Regency. Respondents were randomly selected, namely 10 Islamic Religious Education Teachers consisting of 10 different districts in Semarang Regency. There are two types of data, namely primary data and secondary data. Primary data is obtained by conducting interviews indirectly through a Google Form questionnaire distributed via Whatsapp, while secondary data were obtained through literature and related articles. The results showed that the impact of WFH on GPAI’s performance was influenced by two factors including driving factors and inhibiting factors. The driving factor is the motivation that arises and a sense of responsibility from the GPAI concerned and the inhibiting factor is in the form of problems with device usage skills, limited internet quota, limited internet access, and so on.